Leachate characterization and identification of dominant pollutants using leachate pollution index for an uncontrolled landfill site - S. De; S. Maiti; T. Hazra; A. Debsarkar; A. Dutta (Global Journal of Environmental Science and Management)
Landfill leachates are potential threats for environmental degradation. This study was conducted to determine the leachate quality, to identify the dominant pollutants and to evaluate the leachate pollution potential of an active and closed dumping ground of an uncontrolled municipal solid waste landfill site in Kolkata, India using leachate pollution index. The results of the physico-chemical and biological analyses of leachate indicated that landfill site was in its methanogenic phase. Among the analysed leachate pollutants, TDS, BOD5, COD, TKN, NH3-N, Cl¯, TCB, Pb, and Hg surpassed the leachate discharge standards for inland surface water as specified by the municipal solid waste (Management and Handling) Rules, 2013 for both the dumping grounds. Moreover the concentrations of total Cr and Zn also exceeded the leachate disposal standards for the active dumping ground. The leachate pollution potentialities of both the active and closed dumping grounds were comparable as the overall LPI obtained 34.02 and 31.80 respectively. The overall LPI, LPI organic (LPIor), LPI inorganic (LPIin) and LPI heavy metals (LPIhm) of both the dumping grounds largely exceeded the LPI and sub-LPI values for treated leachate before disposal to the inland surface water. In terms of the individual pollution rating, total coliform bacteria, TKN, NH3-N and Hg were identified as the dominant pollutants and major contributing factors for the leachate pollution potential.